FEATURES AND SCIENTIFIC SIGNIFICANCE OF WRITTEN SOURCES ON THE TIMURID DYNASTY IN THE HISTORY OF KAZAKHSTAN (Journal of history-rus, 2025)
The Objective is to study the culture and history of the states of Central Asia in the Middle Ages. It is very important to creatively master the rich written heritage of past centuries. Persian language data has a special place among written monuments. The purpose of our study is to conduct a historiographical analysis of the research conducted on the basis of these data.In order to obtain the most complete information about the ways of using and transmitting materials in Timurid historiography, the following types of analysis were used: comparative analysis, determining the correspondence of a source to an era, methods of analysis and synthesis of historical sources. During the historical research, the comparative historical method, concrete analysis, retrospective method, current method, and prospective method were used. Narrative historical works by medieval authors, revealing the history of Central Asia in the 14th-15th centuries, mainly consist of works by the “Generation of Amir Timur” group. The works of the reign of Amir Timur are among the data that have not lost their significance from the point of view of scientific validity now. They show not only the policy of Timur and his descendants in relation to neighboring countries and peoples, but also a lot of material about their internal political, economic, ethnic and cultural life. In the article, the author describes the scientific research and determines which works are included in this Timur data. At the same time, he makes a data analysis of the works according to their type, type and content.According to the type, it is indicated that all iron works belong to narrative written data. According to the type, narrative, ironic data are historical chronicles, annals, memoirs, biographies, and diaries.The author looks at the content of the material and clarifies that they can be divided into general and dynastic history groups.